ATIM-44. A PHASE I FIRST-IN-HUMAN TRIAL OF TWO ADENOVIRAL VECTORS EXPRESSING HSV1-TK AND FLT3L FOR TREATING NEWLY DIAGNOSED RESECTABLE MALIGNANT GLIOMA: THERAPEUTIC REPROGRAMMING OF THE BRAIN IMMUNE SYSTEM. (11th November 2019) - Lowenstein, Pedro; A Orringer, Daniel; Sagher, Oren; Heth, Jason; Hervey-Jumper, Shawn; Gerald Mammoser, Aaron; Junck, Larry; Leung, Denise; Umemura, Yoshie; Steven Lawrence, Theodore; Miran Kim, Michelle; Richard Wahl, Daniel; et al.
Abstract: This is an interim report on a first in human Phase I dose escalation trial of the combination of two adenoviral vectors expressing HSV1-TK or Flt3L for the treatment of newly diagnosed, resectable malignant gliomas. Lack of dendritic cells from the brain precludes anti-glioma immune responses. We combined tumor cytotoxicity (Ad-HSV1TK) with recruitment of dendritic cells to gliomas (Ad-Flt3L) to induce anti-glioma immunity. In experimental models this treatment induces powerful cytotoxic CD8 and CD4 T-dependent anti-glioma immunity, immunological memory, and the capacity to recognize neo-antigens. The trial was approved through a FDA-IND, and all institutional cttees. Treatment was administered intraoperatively following complete glioma resection in newly diagnosed tumors. The trial consisted of vector dose escalation, starting at 1x10^9 v.p., and increasing to 1x10^11 v.p. of each vector, through 6 cohorts of 3 patients each. Two cycles of 14 days of valacyclovir were administered to activate HSV1-TK cytotoxicity. Cycle 1 starts on Day 1–3 post surgery for 14 days, and Cycle 2 on Week 8–12. Standard radiation, i.e., 60 Gy in 2 Gy fractions over 6 weeks, with concurrent temozolomide, was followed by cyclic temozolomide. Examination of tumor samples at primary resection and first recurrence show an increase in the infiltration of inflammatory cells. The experimental treatment was well tolerated. An MTD was not reached. There were approx. 248 AEs, and 26 SAEs; these were not linked to treatment. As secondary outcome, median survival of contemporary controls was 604 days, and median survival of trial patients was 742 days. Our results show for the first time that reprogramming of the host's brain immune system to recognize gliomas reveals a new approach for the treatment of highly malignant brain tumors. Clinical trial information: NCT01811992.